Application of the cournot and stackelberg mixed duopoly models for mexican real estate market - Kalashnikov, Vitaly; Flores Curiel, Daniel; González Treviño, Javier (Springer-Verlag Berlin Heidelberg, 2012)
This paper investigates the Mexican real estate market, especially the economy class homes. This sector plays an important role for Mexican social stability. Authors investigate the Cournot and Stackelberg Mixed Duopoly models where there is a competition between a state-owned public firm maximizing domestic social surplus, and a private firm, which maximizes its own profit. Such models are used for modeling markets with low number of participants and high impact of government